2012
DOI: 10.1097/moo.0b013e32835896b4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound imaging of the larynx and vocal folds

Abstract: Future clinical applications could combine conventional B-mode and Nakagami images to allow physicians to simultaneously evaluate the morphology and scatterer properties of laryngeal tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The backscattered statistics of ultrasound echoes measured from biological tissues can be classified as pre-Rayleigh, Rayleigh, and post-Rayleigh distributions 30 . The Nakagami distribution fits well with these three distributions.…”
Section: Methodsmentioning
confidence: 99%
“…The backscattered statistics of ultrasound echoes measured from biological tissues can be classified as pre-Rayleigh, Rayleigh, and post-Rayleigh distributions 30 . The Nakagami distribution fits well with these three distributions.…”
Section: Methodsmentioning
confidence: 99%
“…Echo amplitude distribution measured from tissues can be classified as Rayleigh, pre-Rayleigh, and post-Rayleigh distributions27. The variation of the Nakagami parameter from 0 to 1 corresponds to a change in the echo amplitude distribution from the pre-Rayleigh to Rayleigh distribution; Nakagami parameters higher than 1 indicate that the statistics of the echo amplitude conform to the post-Rayleigh distribution15.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, (i) The envelope image was obtained using the absolute value of the Hilbert Transform of each echo signal filtered using empirical mode decomposition28; (ii) A square window within the envelope image was used to collect local amplitude data for estimating the Nakagami parameter, which is assigned as the new pixel located in the center of the window. The side length of the window was three times the pulse length of the transducer1424252729. The maximum likelihood estimator (MLE) derived by Greenwood30 was selected to calculate the Nakagami parameter because MLE yields a lower variance in estimating the Nakagami parameter313233.…”
Section: Methodsmentioning
confidence: 99%
“…US has been used to successfully evaluate vocal cord masses and abnormal vocal cord movements associated with vocal cord paralysis. 58 Hu et al 28 demonstrated good intra- and interrater reliability (0.723-0.943 and 0.736-0.903 intraclass correlation coefficients, respectively) measurements of the length, width, and thickness of the true and false vocal cords. To date, there have not been any published studies evaluating the ability of sports US to accurately and reproducibly diagnose VCD in athletes.…”
Section: Sonographic Evaluation For Vocal Cord Dysfunctionmentioning
confidence: 98%